BAKTERI ASAM LAKTAT DARI DAGING IKAN PEDA SEBAGAI AGEN PROBIOTIK DAN ENZIM KOLESTEROL REDUKTASE - Hasanah, Uswatun (Universitas Negeri Medan, 2014)
ABSTRACT This study aims to determine the types and characteristics of lactic acid bacteria contained in the Peda Mackerel. The research was conducted in April to June 2013 in the Microbiology Laboratory Biology Department, FMIPA UNIMED. This study used descriptive design using aseptic sampling techniques. Materials used are lactic acid bacteria taken from the Peda Mackerel and grown on MRS medium (de Man Rogosa Sharpe). Based on the research results of the identification and characterization of lactic acid bacteria in Peda Mackerel using Test morphology, Gram staining and Biochemical tests of the obtained 4 types of lactic acid bacteria on the Peda Mackerel. The genus of lactic acid bacteria found include Eubacterium, Lactobacillus, Leuconostoc and Staphylococcus. Characteristics in general is a form of cocci and bacilli, Gram positive, catalase negative, non motile, the optimum temperature of 200C-400C and have type homofermentatif and heterofermentatif fermentation. Kata Kunci : Bakteri asam laktat, peda ikan kembung, probiotik.